PERANCANGAN DINDING PENAHAN TANAH PADA PENANGANAN LONGSORAN JEMBATAN LESAN KABUPATEN BERAU PROVINSI KALIMANTAN TIMUR - IDI, JUNA (KURVA S JURNAL MAHASISWA, 2017)
Retaining wall is a building built to withstand a steep collapse of soil orslopes built in a place where steadiness can not be guaranteed by the slope of thesoil itself. The retaining wall building is used to withstand lateral soil stress causedunstable unstable ground. The building is widely used on projects: irrigation,roads, ports, and others.The landslide that occurred on the Lesan bridge of Berau district of EastBorneo Province has damaged some roads and is feared will damage the abutmentstructure of the bridge if not handled quickly and accurately.The method used in analyzing the stability of the retaining wall in thelandslide is by using Coulomb and Rankine methods, while the method used inanalyzing the carrying capacity of soil occurring using Terzaghi method.From the calculation results can be concluded that, the dimension of theretaining wall is 6 meters high and 1 meter wide body, 0,8 meters thick plate with20 and 25 meters per segment review. Secure the stability of a retaining wall is tobolster however effect the shear, so that the necessary foundation piles is required.